A critical appraisal of the implications of a tactical resignation: some perspectives from South Africa, Eswatini and Lesotho - Maolana, Nkhensani Precious (My University, 2023)
It is settled law that an employee is at liberty to voluntarily end his or her employment contract by resigning subject to serving a notice period. If an employee fails to serve a notice period, that constitutes breach of contract of employment. The usual contractual remedies for breach apply. A familiar problem encountered in labour relations environment is pre-emptive resignation with immediate effect by employees under suspension pending the institution of disciplinary charges. Also prevalent are resignations while disciplinary proceedings are in process. The ultimate of purpose strategic resignation is evasion of accountability for alleged workplace misconduct. Additionally, premeditated resignation is intended to divest the employer of disciplinary jurisdiction with the departing misconducting employee asserting that she has ceased to be the employee. The important question for critical consideration is the legal effect of resignation on the employer’s disciplinary jurisdiction over escaping employee. This question warrants close scrutiny and extended study in light of conflicting authorities on the powers of the employer to discipline an employee post the resignation from South Africa, eSwatini and Lesotho. The message emerging from three leading eSwatini cases namely: Dludlu v Emalangeni Foods Industries [2007] SZIC 21, Rudolph v Mananga College [2007] SZIC 17 and Mdluli v Conco Swaziland Ltd [2009] SZIC 12 is that resignation with immediate effect deprives the erstwhile employer of disciplinary power over the departing employee. Likewise, the Lesotho Labour Appeal Court in Mohamo v Nedbank Lesotho Ltd [2011] LSLAC 9 has held that a former employer has no right to proceed against an employee who has resigned. The implications of the jurisprudential posture from the Kingdoms is that escape artists are shielded from accountability and accorded a free pass to simply disappear into the sunset. While the approach taken in eSwatini cases and by the LSLAC in Mohamo is in line with the minority of judgement Zondo J in Toyota SA Motors (Pty) v CCMA (2016) 37 ILJ 313 (CC); a different stance emerges in key cases such Mzotsho v Standard Bank of SA (Pty) Ltd (unreported case number J2436/18 of 24 July 2018), Coetzee v Zeitz Mocca Foundation Trust (2018) 39 ILJ 2529 (LC), Naidoo v Standard Bank SA Ltd (2019) 40ILJ 2589 (LC) and Mthimkhulu v Standard Bank of SA (2021) 42 ILJ 158 (LC). To illustrate, in Mzotsho, the LC determined that the contractual power to discipline endured despite the fact that an employee resigned immediately upon being given a notice to attend a disciplinary hearing. The clear message from the recent LC decision in Mthimkhulu is that that the resignation before the announcement of a sanction of dismissal has no legal effect.
Thesis (LLM.) -- University of Limpopo, 2023
Keywords: Contract; Employee; Resignation; Employees -- Resignation; Employees -- Resignation -- Law and legislation; Labor discipline